POLYCYSTIC OVARY SYNDROME- BODY MASS INDEX: HORMONAL AND METABOLIC IMPLICATIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Background and aim: Polycystic ovary syndrome (PCOS) is a common endocrine and metabolic disorder affects women in the reproductive age group. PCOS is frequently associated with Obesity. A prominent interplay was noticed between BMI value and hormonal changes accompanying PCOS. The study aims to elucidate role of hormonal factor Anti-Müllerian hormone (AMH) and metabolic factor represented by Myonectin in PCOS patients addressing the effects of BMI on these hormones. Patients and methods: A case-control study was conducted in Baghdad, Iraq. The overall sample size (n = 90) that met the inclusion criteria was divided into two groups as follows: 60 patients who were diagnosed with PCOS and 30 healthy matched women. BMI was calculated using dividing each participants weight in kilograms by their height in meters squared. Blood sample taken for hormonal analysis. Enzyme-linked immunosorbent assay ELISA is used for measuring AMH and Myonectin. Enzyme-linked fluorescence immunoassay (ELFA) used to measure LH and FSH. Results: Body Mass Index (BMI), PCOS patients had significantly higher values than controls (P = 0.002). Anti-Müllerian Hormone (AMH) were notably higher in patients, with a highly significant P value of 0.0001, while myonectin levels were substantially lower in patients compared to controls, with a P value of 0.0001. correlation analysis revealed that AMH levels had a strong negative correlation with Myonectin levels (r = -0.697, p < 0.0001). AMH has strong positive correlation with LH (r = 0.618, p < 0.0001). Regarding BMI, a negative correlation observed with Myonectin and LH, while a positive correlation obtained with AMH (r = 0.4667, p < 0.023). Conclusion: PCOS and BMI is closely related and interacted. AMH and Myonectin could be used as biomarkers for diagnosis of PCOS and its metabolic changes. Obesity is an important feature observed in PCOS patients and shown to influence variable hormonal changes in those patients.